2012
DOI: 10.1088/0022-3727/45/50/505202
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis characteristics of Cu particulates in high-pressure magnetron sputtering plasmas studied by in situ laser-light scattering

Abstract: Abstract.This paper reports the temporal evolution, the dependence on the discharge conditions, and the spatial distribution of Cu particulates synthesized in high-pressure magnetron sputtering plasmas. The spatial distributions of the size and the density of particulates were examined with precision using a two-wavelength laser light scattering technique. We found that more than 50% of Cu particulates in the discharge space had sizes ranging between 100 and 175 nm. The absolute density of Cu particulate was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…However, even though MS-GAS are extensively used to produce NPs of many different materials, very few studies are devoted to the correlation of NP growth dynamics in the high pressure chamber with the parameters of the magnetron discharges [24,27,28]. The formation of NPs in a DC planar magnetron discharge in argon at relatively high pressures (10s of Pa) is also possible [29,30]. In particular experimental studies on the formation of tungsten NPs in high pressure DC planar magnetron argon discharges and their influence on plasma parameters were recently done [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…However, even though MS-GAS are extensively used to produce NPs of many different materials, very few studies are devoted to the correlation of NP growth dynamics in the high pressure chamber with the parameters of the magnetron discharges [24,27,28]. The formation of NPs in a DC planar magnetron discharge in argon at relatively high pressures (10s of Pa) is also possible [29,30]. In particular experimental studies on the formation of tungsten NPs in high pressure DC planar magnetron argon discharges and their influence on plasma parameters were recently done [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The use of Laser Light Scattering (LLS) to detect and follow NPs in the plasma was reported in the literature mainly at low pressure. The dependence of the scattered signal on the size and density of NPs was demonstrated . Roth et al used this technique in silane‐argon RF low pressure plasma to correlate the spatially‐resolved scattered signal with the Si particle growth.…”
Section: Introductionmentioning
confidence: 99%
“…Boufendi et al showed the possibility to detect nanometer size particles by LLS to grasp information on the first stage of both particle nucleation and growth process. Hong et al analyzed the growth of a ‐C:H NPs formed in Ar plasmas with hydrocarbons by means of in situ Rayleigh‐Mie scattered ellipsometry, while Nafarizal and Sasaki measured the spatially‐resolved size and density distribution of Cu particles produced in high‐pressure magnetron sputtering plasma using LLS at two laser wavelengths. In addition, Kamataki et al developed a simple method using 2‐dimensional laser scattering to measure the size and density distribution of NPs created in a low pressure RF plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, HPS has been used to deposit high permittivity dielectrics such as HfO 2 and Gd 2 O 3 [10][11][12]. However, high pressure plasmas are known to be a propitious environment for the formation of dust particles [13] that could be related with the presence of undesirable species in the plasma.…”
Section: Introductionmentioning
confidence: 99%